Relationship Between the Surgical Difficulty of Mandibular Third Molar Extraction Under Local Anesthesia and the Postoperative Level of Salivary Alpha Amylase - Falah Hasan Jumaah, Sahar Shakir Al-Adili, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the relationship between the surgical difficulty of lower third molar removal using time and technique, and the postoperative salivary amylase concentration. Methods: patients submitted for surgical removal of impacted lower wisdom teeth for any indication were included in this prospective cohort study. Three samples of saliva were taken from each patient (preoperative, 48 hours postoperative, and 7 days postoperatively) and the concentration of salivary amylase is measured by Enzyme Linked Immunosorbent Assay (ELISA) kit. The surgical difficulty was assessed using time of operation and the technique for extraction and correlated with the postoperative level of salivary amylase to test if there is any relationship between them, and correlated with other variables including Age, gender, and classification of the impacted lower wisdom tooth (Winter’s and Pell and Gregory’s). Results: 34 patients participated in this study. 15 [44.12%] males and 19 [55.88%] females; 36 impacted teeth were removed (19 in right side [53%], and 17 in the left side [53%] ). The mean ± SD of preoperative, 48 hours and 7 days postoperative salivary amylase concentration were 126.2 ± 31.97, 131.8 ± 48.99, and 127.0 ± 32.09 respectively. 17 impacted teeth were mesioangular, 11 were vertical and 8 were horizontal according to Winter. The surgical difficulty according to time was low in 7, moderate in 14, and high in 15 cases. While difficulty according to technique was low in 5, moderate in 11, and high in 20 cases. The correlation of amylase concentration with the surgical difficulty was (r = 0.23, P= 0.176). Conclusions: there was non-significant correlation between the surgical difficulty (measured by time and technique) and the change in salivary amylase concentration.